2011
DOI: 10.3389/fphys.2011.00055
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide in the RVLM and PVN has No Effect on Cardiovascular Regulation

Abstract: Hydrogen sulfide (H2S) is now recognized as an important signaling molecule and has been shown to have vasodilator and cardio-protectant effects. More recently it has been suggested that H2S may also act within the brain to reduce blood pressure (BP). In the present study we have demonstrated the presence of the H2S-producing enzyme, cystathionine-β-synthase (CBS) in the rostral ventrolateral medulla (RVLM), and the hypothalamic paraventricular nucleus (PVN), brain regions with key cardiovascular regulatory fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
(56 reference statements)
0
10
2
1
Order By: Relevance
“…Contradictory results have been reported by several studies concerning the role of H 2 S in the regulation of cardiovascular function in the RVLM (13,26). These inconsistent results are most likely caused by the instability of the H 2 S donor.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Contradictory results have been reported by several studies concerning the role of H 2 S in the regulation of cardiovascular function in the RVLM (13,26). These inconsistent results are most likely caused by the instability of the H 2 S donor.…”
Section: Discussionmentioning
confidence: 51%
“…Previous experiments have demonstrated that bilateral microinjection of sodium hydrosulfide (NaHS), an H 2 S donor, into the RVLM decreases arterial blood pressure, and the CBS inhibitor hydroxylamine (HA) produces a pressor response (13). Contrary, another study has shown that the microinjection of NaHS into the RVLM has no effect on mean arterial pressure (MAP) (26). Furthermore, conflicting results have been obtained with respect to the effects of H 2 S in the paraventricular nucleus (11,26).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…However, the role of NaHS in regulating blood pressure in the central nervous system (CNS) is still controversial since microinjection of NaHS in RVLM had no significant effect on blood pressure or heart rate (Streeter et al, 2011). Any way, we can exclude a CNS effect of NaHS since the CNS was destroyed in pithed rat.…”
Section: Evidence That Nahs Inhibits the Vasopressor Sympathetic Outflowmentioning
confidence: 96%
“…In isolated blood vessels, H 2 S produces relaxation mainly by activation of K ATP channels (Tang et al, 2010) while in anaesthetised rats NaHS, a donor of H 2 S, mediates hypotension (Ali et al, 2006) although the mechanisms are more complex and several unidentified mechanisms could be involved. Indeed, in anaesthetised rats, hypotension to NaHS is not mediated by nitric oxide release, Kþ channels, BKCa channels, cGMP, release of arachidonic acid metabolites or p450 epoxygenase metabolites.…”
Section: Introductionmentioning
confidence: 99%